2021
DOI: 10.5888/pcd18.200496
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Risk Factors and Screening Among the Uninsured of Tampa Bay: A Free Clinic Study

Abstract: Introduction Uninsured patients with low socioeconomic status are at high risk for developing colorectal cancer (CRC), and data on risk factors and prevalence of CRC in this population are limited. The purpose of this study was to assess the risk factors for CRC in uninsured patients from free clinics in the Tampa Bay area of Florida. Methods We conducted a retrospective cohort study among patients 50 years or older who were provided service at 9 free clinics in the Tam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…27 The importance of screening uninsured patients for colon cancer was highlighted by a prior study conducted of the entire free clinic population included in our study, and described how risk factors for colon cancer are high amongst this uninsured population. 28 Our study found a significant disparity among the patients who completed cervical cancer screenings compared to the insured population. Our study found that 23.9% of cancer survivors and 20.1% of patients without cancer histories received ageappropriate cervical cancer screenings, and had age-appropriate cervical cancer screenings.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…27 The importance of screening uninsured patients for colon cancer was highlighted by a prior study conducted of the entire free clinic population included in our study, and described how risk factors for colon cancer are high amongst this uninsured population. 28 Our study found a significant disparity among the patients who completed cervical cancer screenings compared to the insured population. Our study found that 23.9% of cancer survivors and 20.1% of patients without cancer histories received ageappropriate cervical cancer screenings, and had age-appropriate cervical cancer screenings.…”
Section: Discussionmentioning
confidence: 58%
“…27 The importance of screening uninsured patients for colon cancer was highlighted by a prior study conducted of the entire free clinic population included in our study, and described how risk factors for colon cancer are high amongst this uninsured population. 28 …”
Section: Discussionmentioning
confidence: 99%
“…15 16 17 The prevalence of all risk factors is higher among uninsured populations. 18 19 The intersection of neighborhood-level factors, such as access to healthy food, and an individual's insurance status compound risk. For example, uninsured individuals are more likely to live in low-income neighborhoods and food deserts, which have been linked to higher CRC incidence and mortality.…”
Section: Barriers To Colorectal Surgery Care Among Uninsured and Unde...mentioning
confidence: 99%
“…It is also crucial to recognize the significant impact of socioeconomic inequalities on screening rates because early screening can influence disease incidence, prevalence, and outcomes [24][25][26][27]. Studies have identified several socioeconomic barriers, such as lower educational attainment, income inequality, and limited access to healthcare facilities, contributing to lower screening rates in disadvantaged populations [16,28]. It is important to recognize that these socioeconomic factors may intersect and influence each other (e.g., individuals with lower education levels may also face financial constraints and limited access to healthcare facilities), exacerbating challenges for disadvantaged populations.…”
Section: Systemic Challenges: Screening Implementation and Socioecono...mentioning
confidence: 99%